Wax-Induced Episodic Hemolysis in a Patient with Co-Inheritance of Sickle Cell Anemia and G6PD Deficiency - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Both sickle cell anemia (SCA) and glucose-6-phosphate dehydrogenase (G6PD) deficiency are common genetically transmitted disorders associated with hemolytic anemia, with a high prevalence in sub-Saharan Africa. Co-inheritance of both diseases has been reported in Nigeria where the prevalence of each disease is high. However, a high index of suspicion is needed to diagnose the co-existence of both disorders in the same individual. Here, we present an unusual case of a 32-year-old dentistry student who was known to have SCA since the age of one year. He presented with episodic exacerbation of jaundice and passage of dark-colored urine following skin and inhalational exposure to wax (polycyclic aromatic hydrocarbons) used for reconstructive dental practical sessions. After investigations, he was found to have G6PD deficiency. This report underscores the importance of screening for G6PD deficiency in male patients with SCA presenting with episodic symptoms of hemolysis.